Old King Cole and friend - Straw, Wendy (Leicester, United Kingdom sweet cherry Publishing, 2020)
Join in the fun as your all-time favourite children's nursery rhymes are brought to life by Wendy Straw's charming illustrations
Rhymes and songs
Keywords: Counting-out rhymes; Nursery rhymes